The revivalists : a novel - Hood, Christopher M. (Harper, an imprint of HarperCollinsPublishers, 2022)
"When their daughter joins a cult 3,000 miles away in Bishop, California, Bill and Penelope set out on a harrowing journey across the hollowed-out remains of America to save her, and even though the world has changed, their hopes and fears remain the same"--